An Unusual Case of Periosteal Glomus Tumor at the Metacarpal Base Presenting as Type II CRPS: Case Report. (January 2021) - Smith, Dean W.
Background: An unusual case involving a middle-aged male with a 9-year history of presumptive chronic regional pain syndrome (CRPS) and ulnar neuropathy was referred for failure in treatment.Methods: On presentation, the patient was requesting an amputation of his arm. However, work-up uncovered a periosteal extra-digital glomus tumor on the base of the small finger metacarpal.Results: Surgical excision of the lesion resulted in rapid resolution of his pain and normal hand function was ultimately restored.Conclusions: Glomus tumors account for up to 5% of all soft tissue tumors of the upper extremity, occurring most frequently within or adjacent to the nail bed. Time from onset of symptoms to correct diagnosis may not be established for many years, especially with atypical tumor locations. Although glomus tumors have been widely reported, atypical locations of these tumors should be included in the differential diagnosis for patients with unusual chronic pain or neuropathy. Furthermore, when evaluating a chronic pain patient, our findings support the opinion that assignment of the diagnosis of CRPS should only be a diagnosis of exclusion.